Conjoined fetal twins in a harbor seal (Phoca vitulina) - Olson, Jennifer K. (Western CEDAR, 2014)
Harbor seals (Phoca vitulina) are the most abundant marine mammal in the Salish Sea and have been used as indicators for contaminants throughout the region. On July 11, 2013, an adult female harbor seal stranded on a private beach in Olga, WA (48° 36' 2.79", -122° 49' 45.92") and was collected by the San Juan County Marine Mammal Stranding Network. Gross examination indicated that the animal was in good nutritional condition and likely died as a result of dystocia (birthing difficulty). The seal was pregnant with male ischiopagus conjoined twins that were oriented at a 180° angle. The more caudal head protruded from the vulva and the more cranial head was retained in utero. Four pairs of flippers (two sets of fore-flippers and two sets of caudal flippers) were present. CT scan showed that the twins were joined at the caudal aspect of the thoracic spine/cranial lumbar spine where there was fusion of the spinal canal and vertebral bodies as well as significant spinal angulation and distortion. The fetus was incompletely developed, as evidenced by the presence of a partial lanugo coat, deciduous incisors and fetal heart circulation. The fontanels for both heads were not fused and were incompletely mineralized. Multifactorial contaminants, chromosomal aberrations, infectious agents and other entities have been known to cause fetal malformations in domestic animals. Toxicologic screening for a variety of organic and inorganic contaminants in liver, kidney and adipose samples was unremarkable. We hypothesize that this congenital anomaly was idiopathic, not due to contaminants, and related to disordered embryonic migration and fusion.